2018
DOI: 10.1021/jacs.8b11230
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Cages in Chemically Robust MOFs Created by a Large Number of Vertices with Reduced Connectivity

Abstract: We report the design and synthesis of two metal−organic frameworks (MOFs) with permanent porosity, MOF-818 and MOF-919, using a small ditopic organic linker, 1H-pyrazole-4-carboxylic acid (H 2 PyC), 0.4 nm in length. Three mesoporous cages of unprecedented polyhedra are identified in these MOFs, a wuh cage in MOF-818 and yys and liu cages in MOF-919, with diameters of 3.8, 4.9, and 6.0 nm, respectively. The ditopic H 2 PyC linker functions as the edge in the structure, while two types of metal-containing secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
121
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 56 publications
6
121
0
1
Order By: Relevance
“…It should be derived from the decomposition of H 2 PyC concerning the collapse of the MOF-818 framework. Therefore, it can be concluded that the MOF-818 showed good thermal stability below 280 °C, which is consistent with the previous reports [50].…”
Section: Characterizationssupporting
confidence: 92%
See 4 more Smart Citations
“…It should be derived from the decomposition of H 2 PyC concerning the collapse of the MOF-818 framework. Therefore, it can be concluded that the MOF-818 showed good thermal stability below 280 °C, which is consistent with the previous reports [50].…”
Section: Characterizationssupporting
confidence: 92%
“…2a, the data showed an intense peak at 3.09° and five other peaks at 4.96°, 5.80°, 6.05°, 7.00° and 7.60°, which were indexed to the (111), (220), (311), (222), (400) and (331) diffractions, respectively. The diffraction peaks of MOF-818 matched well with the simulated one in the literature [50]. No peaks corresponding to CuO or ZrO 2 were found.…”
Section: Characterizationssupporting
confidence: 82%
See 3 more Smart Citations